Disentangling and locating the ''Global Right'': Anti-gender campaigns in Europe - Paternotte, David; Kuhar, Roman (Politics and Governance, 2018)
This article examines the development of campaigns against “gender ideology” in Europe, leading to the emergence of a specific family of mobilizations that we call anti-gender campaigns. These campaigns, started in the mid-1990s as a Catholic project in reaction to the results of the UN conferences of Cairo and Bejing, but developed significantly in several European countries after crucial encounters with right-wing populism. While recognizing the importance of these crossovers, we contend the interpretation that mobilizations against “gender ideology” and right-wing populism are the two faces of the same coin, and we plead for a more complex understanding of the ways in which distinct—and sometimes competing—projects can converge in specific settings. We argue that research on the “Global Right Wing” should therefore disentangle the various components of this phenomenon, and locate them in concrete settings. We show that this research strategy allows us to better grasp the specificities of each project and the ways in which they interact. Opening our eyes on crucial developments in contemporary Europe, this strategy also prevents researchers from falling into the trap of a global and unqualified backlash against everything achieved in terms of gender and sexuality in the last decades.
Keywords: discipline; europe; mouvements anti-genre; régions géographiques; sciences humaines; sociologie; thématiques; violences